Experimental Analysis and Optimization of Mechanical and Physical Properties of Light-Weight Bulk Molding Compound by Design of Experiment. Issue 4 (18th November 2020) - Rajaee, Pouya; Ashenai Ghasemi, Faramarz; Fasihi, Mohammad; Saberian, Mohammadhossein
Abstract: The low deflection at break of unsaturated polyester resin-based composites is a problem in many industrial applications. In this work an attempt was made to optimize the bulk molding compound formulation with respect to styrene–butadiene rubber (SBR) and fumed silica (FS) components to obtain optimum mechanical properties (flexural strength and deflection at break) and density. To this end an experimental design was used to study the influence of each parameter and its interaction with the responses (density, flexural strength, and deflection at break). Accordingly, four levels of SBR (0, 10, 20, and 30 wt%) and three levels of FS (0, 1, and 3 phr) were used. The addition of FS increased the flexural strength and density of the composites, but lowered their deflection at break, while the effect of SBR was almost vice versa. Based on the desirability function, the 10 wt% SBR without FS was suggested to be the optimum composition providing the best density, strength, and deformability. It was also seen that adding 3 phr FS increased the flexural strength, but without the desired density and deflection at break. Moreover, the R 2 obtained from the ANOVA and plots of normal probability showed good compliance between the experimental results and those predicted using a full factorial model.